FACTORS RELATED TO THE EVENT OF STUNTING TOddlers in the WORK AREA OF THE BOJONEGORO KANOR HEALTH CENTER - Sarni Anggoro (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2021)
Stunting is a condition of failure to thrive in children under five. One of the signs that appears is a child with a stunted stature when he reaches the age of 2 years. Stunting occurs due to lack of nutritional intake. Many factors affect the provision of nutritional intake by parents to their toddlers. This study aims to determine what factors are associated with the incidence of stunting in the working area of ​​the Kanor Bojonegoro Health Center. This research uses quantitative descriptive research with cross sectional design. Respondents in this study were all mothers who have toddlers in the working area of ​​Kanor Health Center, Bojonegoro, as many as 128. The sampling technique used was accidental sampling. This research was conducted in January 2021. The data collection technique used in this study used a questionnaire on parenting, knowledge and income. The questionnaire has been tested for validity and reliability. Analysis of the data used to test the relationship between variables is the chi square test. The results showed that the majority of maternal parenting patterns were in the bad category, with poor knowledge of the mother and with income that was in the poor category. The correlation results show that the p-value of each variable is <0.05. The conclusion of the study showed that the factors of maternal parenting, mother's knowledge about stunting and family income were related to the incidence of stunting.